The Analysis of Hail Based on Atmospheric Conditions and Himawari-9 Satellite: Case Study of Surabaya City, March 20, 2023 - Mashuri, Imawan; Amri, Sayful; Aslama Afghani, Fadhli; Muhammad Aslam, Fadhil (Universitas Negeri Semarang, 2025)
Hail is a rare extreme weather phenomenon in Indonesia. On March 20, 2023, hail occurred in Surabaya City. The research was conducted to analyze the hail based on atmospheric conditions and the Himawari-9 satellite. Analysis of the global scale showed anomalies in sea surface temperature in the Southeast Indian Ocean. Regionally, a monsoon shear line and significant low-level moisture transport from the South Java Sea caused convergence in the Surabaya. Locally, there was a significant increase in relative humidity by 10%, and a surface temperature decrease of 3.2°C resulted in wetter surface weather. The occurrence of hail was also supported by upper air conditions, with four indices (CAPE, LI, TT, and SWEAT) falling within the moderate category. In contrast, CIN was categorized as low, while KI increased from moderate to high. A moderate CAPE index in the mid-level updraft of moist air resulted in the maximum hail size. Clouds reached the freezing level in the mid-level atmosphere at 5048 meters and 4776 meters. The RGB Day Microphysics technique using Himawari-9 satellite imagery identified overshooting tops and a drastic decrease in top cloud temperature reaching -82.5°C, indicating the presence of a strong updraft and the formation of convective clouds that surpassed the freezing level.